Gas‐Phase 3D Printing of Functional Materials. Issue 12 (29th October 2020) - de la Huerta, Cesar Arturo Masse; Nguyen, Viet H.; Sekkat, Abderrahime; Crivello, Chiara; Toldra‐Reig, Fidel; Veiga, Pedro Brandao; Quessada, Serge; Jimenez, Carmen; Muñoz‐Rojas, David
Abstract: Spatial atomic layer deposition (SALD) is a recent approach 100 times faster than conventional atomic layer deposition (ALD), even at atmospheric pressure. Previous works exploited these assets focussing on high‐rate, large‐area deposition for scaling‐up into mass production. Conversely, this work shows that SALD indeed represents an ideal platform for area‐selective deposition of functional materials by proper design and miniaturization of close‐proximity SALD heads. In particular, the potential offered by 3D printing is used to fabricate low‐cost customized close‐proximity heads, which can be easily designed and modified to obtain different deposition areas, free‐form patterns, and even complex multimaterial structures. Finally, by designing a miniaturized head with circular concentric gas channels, 3D printing of functional materials can be performed with nanometric resolution in Z. This constitutes a new gas‐phase 3D printing approach. Because the process is based on ALD reactions, conformal and continuous thin films of functional materials can be printed at low temperatures and with high deposition rate in the open air. This approach represents a new versatile way of printing functional materials and devices with spatial and topological control, thus extending the potential of SALD and ALD in general, and opening a new avenue in the field of area‐selective deposition of functional materials. Abstract : An open‐air gas‐based deposition technique is developed to perform area‐selective deposition of functional materials with topological control. The technique is based on customized close‐proximity spatial atomic layer deposition injection heads easily fabricated by 3D printing. Free‐form patterns and multilayers of functional oxides are performed without pre‐patterning steps, in just minutes and with nanometric resolution in the Z axis.